The use of social networks in the learning process of future engineers - Babych, T. P. (Problems of Engineer-Pedagogical Education, 2018)
The article discusses the use of social networks as a means of training future engineers. The article is to study and determine the main directions of social networking and search userfriendly tools for learning. To study this phenomenon, a study was conducted among students of different profiles on their use of social networks. Based on a survey of young people determined how social networks help them in the learning process. The survey form was created online survey based on Google Form. The problem of using new technologies in the learning process are quite important in the development of modern higher education. Especially when preparing future engineers. Because modern engineer is the creator of a new and modern technology is not standing still, and require constant improvement and development. Technologies change, which in turn requires students to ongoing development and improvement of their knowledge. It's enough to effectively use social networks, which are very effective and convenient tool for teaching students, as well as a means of improving the knowledge of students and teachers. We can not forget the handy tool of communication which is the social network. Then analyzed: the most popular tools used in teaching social networks. It can be concluded that the use of social networks has prospects for training engineers.